2007
DOI: 10.1007/s10640-007-9131-6
|View full text |Cite
|
Sign up to set email alerts
|

Environmental groups in monopolistic markets

Abstract: We examine a market in which a monopolistic firm supplies a good. The production of the good causes damage to the environment. Consumers are heterogeneous with respect to their disutility of the environmental damage. An environmental group can enter the market and set up a campaign in order to influence consumers' preferences. We characterize the equilibrium of the resulting entry-deterrence game and investigate its properties. It turns out that the aggregated environmental damage is lowest if the firm is able… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…The idea of environmentalists conflicting with firms and how this antagonistic relationship can affect environmental quality and social welfare have already been investigated by a large strand of literature (see e.g., Friehe 2013; Sartzetakis et al 2012;Petrakis et al 2005;Heyes and Maxwell 2004;Liston-Heyes 2001). The present paper is closest to Heijnen and Schoonbeek (2008) who examine a market in which a monopolistic firm supplies an environmentally unfriendly good. They characterise the equilibrium of an entry deterrence game, where an EG can enter the market and set up a campaign to inform consumers about the environmental damage.…”
Section: Introductionmentioning
confidence: 88%
“…The idea of environmentalists conflicting with firms and how this antagonistic relationship can affect environmental quality and social welfare have already been investigated by a large strand of literature (see e.g., Friehe 2013; Sartzetakis et al 2012;Petrakis et al 2005;Heyes and Maxwell 2004;Liston-Heyes 2001). The present paper is closest to Heijnen and Schoonbeek (2008) who examine a market in which a monopolistic firm supplies an environmentally unfriendly good. They characterise the equilibrium of an entry deterrence game, where an EG can enter the market and set up a campaign to inform consumers about the environmental damage.…”
Section: Introductionmentioning
confidence: 88%
“…The view that advertisement exhibits some degree of economies of scale is widely acceptable by both theoreticians and practitioners. 12 Moreover, in the most recent literature an S-shaped response function to advertisement has been used extensively (see for example Feinberg (2001)). The S-shaped response function implies increasing marginal returns to advertising for low advertising levels followed, after an inflection point, by decreasing marginal returns.…”
Section: The Modelmentioning
confidence: 99%
“…Moreover, the importance of information provision has been established by many studies in the case of public antismoking campaigns. 5 3 Liston-Heyes (2001), Heijnen and Schoonbeek (2008) and Heyes and Maxwell (2004) examine the role and the effectiveness of environmental groups in informing consumers. These works examine also the interplay between the environmental group and the polluting firms.…”
Section: Introductionmentioning
confidence: 99%
“…In a further study, Junge et al (2011) found that complex landscapes, with mixed land use and a large proportion of wildflower field margins, are appreciated by Swiss residents and positively influence scenic beauty. Heijnen and Schoonbeek (2008) reported that environmental groups could influence consumer preferences through advertising campaigns: even though consumers are heterogeneous with respect to their disutility of the environmental damage caused by a product. Van der Made (2008) concluded that interest groups could influence consumer choice by disseminating information on production practices and thereby effectively introducing vertical product differentiation.…”
Section: Introductionmentioning
confidence: 99%